THE USE OF SONG MEDIA TO INCREASE STUDENTS’ VOCABULARY IN ENGLISH SUBJECTS AT SMP NEGERI 8 SATU ATAP TONDANO - Yustika Hanorsian; Ignatius J. C. Tuerah; Rinny Rorimpandey (Program Studi Pendidikan Bahasa Inggris, 2023)
This research aims to determine the effect of using song media on increasing students' vocabulary in the English subject for Class VII students at SMP Negeri 8 Satu Atap Tondano. This research uses a pre-experimental design with a one group pretest-posttest design. This research was carried out at SMP Negeri 8 Satu Atap Tondano. The research sample was class VII, totaling 5 students. The pretest and posttest were given as research instruments, with a total of 18 questions. The research results show that the use of song media can increase students' vocabulary. This statement is proven by the students' posttest average score (74.38) with a standard deviation of 13.37 which is greater than the pretest average score (41.06) with a standard deviation of 6.35. Apart from that, the results of the hypothesis test show that the T-test value (4.039) is greater than the T-table (2.131). Therefore, it can be concluded that the use of song media is effective in increasing the English vocabulary of class VII students at SMP Negeri 8 Satu Atap Tondano.